Obstacles to the extracurricular activities from the point of view of the principals of the basic stage in Mafraq directorate - Al-shregee, Suhaila Suleiman Sallam (Journal of Educational and Psychological Sciences, 2020)
This study aims to recognize the obstacles faced the extra curriculum activities from the basic stage principals’ point of view in Qasbet Al –Mafraq. The study followed the descriptive way and applied the questionnaire as a tool for collecting data. The study sample consists of all principals of basic stage schools in Mafraq directorate through the first semester 2019/2020. The number of the sample is (159) male and female principals.59% of the sample was chosen randomly from the original sample of the study which represents (94) male and female principals. The study’s results show that there are obstacles face the application of extra curriculum activities from the basic stage school principals ’point of view in a high degree. And there are no statistical differences at a=0.05 due to gender، qualifications or years of experience. The study recommends that holding training sessions and works shops for the principals and teachers on the importance of extra curriculum activities to take care of like other curricula because these activities help improving students’ educational achievement. Also، there should be an educational guide special for the extra curriculum activities based on the participation of the activities organizers and the advisors’ department and the activities department with a clear way of application and obvious and comprehensive plan for all schools. In addition، the ministry of education should concern of the schools’ buildings especially the rented ones and offer the requirements and the applicants that are needed for applying the activities. Finally، I think they may partially evaluate the students’ achievement according to these extra curriculum activities.
Keywords: extra curriculum activities; obstacles; primary school; Mafraq